IMPROVING STUDENTS’ READING COMPREHENSION THROUGH LISTEN-READ-DISCUSS (LRD) STRATEGY AT SMP KRISTEN KAKASKASEN - Tuuk, Gloria S.; olii, Sanerita T.; Hampp, Paula (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
The purpose of this research is to evaluate how well the LRD strategy works to improve reading comprehension. Using a methodological framework with pre- and post-test assessments, the study investigates the relationship between eighth-grade students’ increased reading comprehension levels and their implementation of the LRD strategy. The dynamic nature of English language instruction makes the choice of a suitable approach crucial. Due to the complexity of language acquisition, creative methods are needed, taking into account the interests of the students as well as existing arrangements and provisions. The findings demonstrate the LRD strategy’s strong positive effects, with students’ growth attributed mostly to their intrinsic drive and active participation. Due to the strategy’s inherent flexibility, training may be tailored to each student’s ability level. These results highlight the LRD strategy’s ability to enhance reading comprehension results. Because of the strategy’s flexibility and the characteristics that have been found to be important, it can be used to students of different skill levels, which has significance for middle school teachers and policymakers.